AB0300 LIVER DISORDERS DURING RHEUMATOID ARTHRITIS. (June 2019) - Tekaya, Aicha Ben; Zouaoui, Khaoula; Mahmoud, Ines; Saidane, Olfa; Hammamia, Mohamed Ben; Tekaya, Rawdha; Abdelmoula, Leila
Abstract : Background: Hepatic disease in rheumatoid arthritis (RA) are rare, but can be impactful for patients. Though some hepatic manifestations are directly related to RA, whereas others may be sequelae of treatment or caused by concomitant autoimmune diseases. Objectives: We have tried through this study to focus on the liver disorders during the monitoring of rheumatoid arthritis and to identify the different etiologies. Methods: This is a retrospective descriptive study of patients with rheumatoid arthritis (ACR-EULAR 2010 criteria) followed a rheumatology department between 2012 and 2018 with liver function disorder. We have specified the epidemiological, clinical, biological and therapeutic characteristics and the different explorations carried out for these patients. Results: We included 61 patients in our study (3 men and 58 women). Mean age was 52.13 years [26-82]. Average duration of RA was 9.2 years [0.5-30]. Mean DAS28 was 5.95 [3-8.33]. RA was immunopositive in 88, 5% of the cases and erosive in 93, 44% of the cases. Most of patients received symptomatic treatment (98% paracetamol, 87% non-steroidal anti-inflammatory drugs, 84% corticosteroids).As for conventional csDMARD, 72% of patients were treated with methotrexate, 8.2% with anti-malarial, 22.95% with salazopyrine and 11.47% with leflunomide. Three patients received biologic DMARDs (1 rituximab and 2 TNF-Blockers). Hepatic disorders were:cholestasis (95%), cytolysis (33%) and concomitant cytolysis and cholestasis (28%). The etiological investigation undertaken linked these disorders of the liver function disorders to the RA treatment in 50% of the cases.Methotrexate was incriminated in the genesis of this liver enzyme abnormalities in 14 cases, the salazopyrine in 2 cases, the leflunomide in 1 case, paracetamol and nonsteroidal anti-inflammatory drugs in 11 cases and rituximab in 1 case. Hepatic immunological investigation was negative in all cases. We have not noted any hepatitis B seroconversion. Two patients had hepatitis C. One patient presented active hepatitis C serology with signs of fibrosis (A2F2) at the liver biopsy puncture. Abdominal ultrasound showed signs of non-alcoholic fatty liver disease in 34.42% of cases. The biopsy puncture of the liver was performed in 9 patients showing chronic hepatitis lesions (n=1), hepatic atrophy (n=1), steatosis with portal and peri-sinus fibrosis (n=1). The etiological investigation was negative in 10% of cases. Conclusion: In our study, the liver function disorders during RA are in half of the cases of iatrogenic origin. This requires rigorous monitoring of patients followed for RA in order to improve their management. Disclosure of Interests: None declared